2013
DOI: 10.1186/1476-7120-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Volume quantification by contrast-enhanced ultrasound: an in-vitro comparison with true volumes and thermodilution

Abstract: BackgroundContrast-enhanced ultrasound (CEUS) has recently been proposed as a minimally- invasive, alternative method for blood volume measurement. This study aims at comparing the accuracy of CEUS and the classical thermodilution techniques for volume assessment in an in-vitro set-up.MethodsThe in-vitro set-up consisted of a variable network between an inflow and outflow tube and a roller pump. The inflow and outflow tubes were insonified with an ultrasound array transducer and a thermistor was placed in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…[10][11][12][13] Moreover, normalized left atrial transit times are correlated with invasive left ventricular pressure measurements. 14,15 CEUS-derived PTT correlates well with true volumes in an in-vitro setup, 16 with PTT measured via MRI and with levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP). 1 Choi et al 17 showed that cardiac output measured by right heart catheterization correlates with transit times measured with contrast echocardiography.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[10][11][12][13] Moreover, normalized left atrial transit times are correlated with invasive left ventricular pressure measurements. 14,15 CEUS-derived PTT correlates well with true volumes in an in-vitro setup, 16 with PTT measured via MRI and with levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP). 1 Choi et al 17 showed that cardiac output measured by right heart catheterization correlates with transit times measured with contrast echocardiography.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, normalized left atrial transit times are correlated with invasive left ventricular pressure measurements . CEUS‐derived PTT correlates well with true volumes in an in‐vitro setup, with PTT measured via MRI and with levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) . Choi et al .…”
Section: Introductionmentioning
confidence: 94%
“…CEUS has been validated for accurately measuring visceral blood flow against a number of proven technologies. Numerous in vitro and in vivo studies have validated the accuracy of CEUS in assessing microvascular blood flow, demonstrating close correlation with thermodilution (Herold et al, 2013), mechanically controlled flow (Wei et al, 1998) and end-organ microvascular perfusion (Rim et al, 2001;Wei et al, 2001).…”
Section: Introductionmentioning
confidence: 87%
“…ODM has been validated against PAFC thermodilution techniques in a 61 number of patient populations [7]. ODM has allowed a number of algorithms to be 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 [17], mechanically controlled flow [18] and end organ microvascular 87 perfusion [19], [20] . tracking changes in MBF of the intra-abdominal viscera [21,…”
mentioning
confidence: 99%
“…Prior studies have compared echocardiographically-derived and invasively determined PBV in vitro (4) and in patients undergoing cardiac surgery (5). PBV is related to left atrial (LA) pressure (6).…”
Section: Introductionmentioning
confidence: 99%